2021
DOI: 10.15294/jpii.v10i2.26775
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Gender Differential Item Functioning in Tegal Students' Scientific Literacy Skills with Integrated Science (SLiSIS) Test Using Rasch Model

Abstract: The emergence of Differential Item Functioning (DIF) indicates an external bias in an item. This study aims to identify items at scientific literacy skills with integrated science (SLiSIS) test that experience DIF based on gender. Moreover, it is analyzed the emergence of DIF, especially related to the test construct measured, and concluded on how far the validity of the SLiSIS test from the construct validity of consequential type. The study was conducted with a quantitative approach by using a survey or non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 43 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…Gender bias remains a long debate within science education literature. Certain studies report that females will be beneficiaries through science education and performance is significantly distinct among students' gender (Ramdani et al, 2021;Susongko et al, 2021). Due to the limitation of the research focus of this paper, interested readers would be offered to study this in a more depth analysis using multiple methods quantitatively, qualitatively, or combined.…”
Section: Resultsmentioning
confidence: 99%
“…Gender bias remains a long debate within science education literature. Certain studies report that females will be beneficiaries through science education and performance is significantly distinct among students' gender (Ramdani et al, 2021;Susongko et al, 2021). Due to the limitation of the research focus of this paper, interested readers would be offered to study this in a more depth analysis using multiple methods quantitatively, qualitatively, or combined.…”
Section: Resultsmentioning
confidence: 99%
“…The type of validity applied is Messick Validity (Messick, 1995), which includes content validity, psychometric validity, and construct validity consisting of content aspects, substantive aspects, structural aspects, and external aspects. Construct validity uses the Rasch modeling application based on the concept of Messick validity, which has been formulated by Susongko, (2016), as described in Table 1 below.…”
Section: Methodsmentioning
confidence: 99%
“…After we conducting need analysis in the preliminary research, there is currently no study on the development of scientific literacy instruments in Indonesia that combines the three dimensions of scientific literacy in a comprehensive manner. Similarly, few researchers have used the Rasch model approach to validation or digital applications in their presentations (Susongko, 2016;Susongko et al, 2019;Susongko et al, 2021) The Scientific Reasoning Test is a test that measures scientific reasoning ability for high school students or its equivalent. Scientific reasoning basically consists of abilities in: ( 1 The Scientific Reasoning Test is basically inseparable from the three aspects of the Scientific Literacy Test.…”
Section: Introductionmentioning
confidence: 99%
“…Involving DIF analysis of items to assess the quality of a four-tier diagnostic instrument has never been reported before [3], [16], [17], [26], [28]. However, the appearance of items in the 4T-HTDT experiencing DIF does not always indicate the weakness of a measuring instrument [53]. Several studies showed the linearity of the effect of a large sample size on the number of items experiencing DIF [54].…”
Section: Differential Item Functioning (Dif) Of Respondents' Demograp...mentioning
confidence: 99%